Altered lives, enduring community : Japanese Americans remember their World War II incarceration - Fugita, Stephen (The Scott and Laurie Oki series in Asian American studies., 2004)
"Altered Lives, Enduring Community examines the long-term effects on Japanese Americans of their World War II experiences: forced removal from their Pacific Coast homes, incarceration in desolate government camps, and ultimate resettlement. The authors use data from the first-ever, representative survey of a community of Japanese Americans who were imprisoned during World War II, conducted as part of Seattle's Densho: Japanese American Legacy Project. Their often poignant account presents the contemporary, post-redress perspectives of former incarcerees and reveals the incarceration's consequences for their lives."--Jacket.